TREND PEMBELIAN ONLINE REMAJA DI MASA PANDEMI (STUDI KASUS PADA REMAJA KONSUMEN SHOPEE DI BANDAR LAMPUNG) - Fitriyani, Tina; Aprilia, deddy; Nugeraha, Prasetya (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
This study aims to determine the effect of brand image, flash sale, promotion on consumer buying interest in the shopee e-commerce application in Bandar Lampung. This type of explanatory research with a quantitative approach. The sampling technique used purposive sampling with a sample of 400 respondents. The data were obtained from a questionnaire using a Likert scale. The data analysis in this study used multiple linear analysis with SPSS. Based on the results of research and data analysis, it shows that brand image, flash sale, promotion simultaneously affect consumer buying interest by 69.6%. Then the partial test results of each variable show that brand image has a significant effect on consumer buying interest by 19.7% and flash sale has a significant effect on consumer purchase interest by 45.4%, while promotion has a significant effect on consumer purchase interest. amounted to 25.1%. So that the Shopee e-commerce application can increase consumer buying interest.